INTED2019 Proceedings 2019
DOI: 10.21125/inted.2019.0328
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Financial Literacy Level of Ecuadorian Polytechnic University Students? An Essay to Evaluate Their Performance

Abstract: University students were evaluated about financial literacy (FL) with a customized survey based on the contributions of many research studies including the OECD toolkit. Demographic and socioeconomic variables were related to three dimensions of FL, financial knowledge (FK), financial behavior (FB) and financial attitude (FA) as the content of this survey. Students with better financial background reached better FL scores and students without this background, but strong numeracy formation obtained the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…The higher stock market literacy scores for master's graduates joined the previous findings with higher educational attainment results [9] [18].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The higher stock market literacy scores for master's graduates joined the previous findings with higher educational attainment results [9] [18].…”
Section: Discussionsupporting
confidence: 68%
“…In a recent study on university students in Ecuador from Mendez et al 2019, they revealed low levels of financial knowledge. About 51% of the students obtained a score between 0% and 40%, out of a maximum score of Financial Knowledge of 100% [9]. According to other findings research, this precedent denotes an impediment of great significance to the stock market development.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation